2020
DOI: 10.1186/s12951-020-00634-1
|View full text |Cite
|
Sign up to set email alerts
|

p62/SQSTM1 accumulation due to degradation inhibition and transcriptional activation plays a critical role in silica nanoparticle-induced airway inflammation via NF-κB activation

Abstract: Background: Most nanoparticles (NPs) reportedly block autophagic flux, thereby upregulating p62/SQSTM1 through degradation inhibition. p62 also acts as a multifunctional scaffold protein with multiple domains, and is involved in various cellular processes. However, the autophagy substrate-independent role of p62 and its regulation at the transcriptional level upon NPs exposure remain unclear. Results: In this work, we exposed BEAS-2b cells and mice to silica nanoparticles (SiNPs), and found that SiNPs increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…They found a significantly higher accumulation of SQSTM1 in smokers as compared to nonsmokers, and an increased severity of COPD. Wu et al ( 2020 ) found that the accumulation of SQSTM1 plays a critical role in airway inflammation induced by nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…They found a significantly higher accumulation of SQSTM1 in smokers as compared to nonsmokers, and an increased severity of COPD. Wu et al ( 2020 ) found that the accumulation of SQSTM1 plays a critical role in airway inflammation induced by nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…They found a significant higher accumulation of SQSTM1 in smokers as compared to nonsmokers, and an increased severity of COPD. Wu et al [42] found that the accumulation of SQSTM1 plays a critical role in airway inflammation induced by nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…3C). Several TFs such as activating transcription factor 3 (ATF3), kruppel like factor 5 (KLF5), and specificity protein 1 (SP1) and the previously reported TF of p62, nuclear factor E2-related factor (Nrf2), (13,14) were identified to stimulate the p62-Luc reporter activity as well as the mRNA level of p62 co-transfected with LINC01134, among which SP1 was the most vigorous stimulators in both luciferase and quantitative PCR assays, indicating that SP1 was the most possible TF responsible for LINC01134 up-regulation of p62 transcription (Supporting Fig. S4A,B).…”
Section: Linc01134 Up-regulates P62 Expression By Enhancing the Recru...mentioning
confidence: 99%